Aplikasi Pengelolaan Sampah Terpadu Di Kelurahan Tembalang Kota Semarang - Elzha Af’idatul Himmah; Nur Endah Wahyuningsih; Tri Joko (Jurnal Kesehatan Masyarakat (Undip), 2014)
Garbage is a classic problem for developing countries such as Indonesia, high population density and human activities lead to a growing amount of waste that is produced also increased and varied. The total population of around 47,763 souls Tembalang Village consists of 5,334 natives and newcomers. High number of population and environmental impacts of solid waste problems especially. Everyday TPS got a shipment exceeding 24 m3 of garbage containers. So that not all waste can be transported to the landfill. Based on data from Semarang City Health Office in 2012-August 2013 in the village Tembalang there were 43 cases of Dengue Hemorrhagic Fever. As for cases of diarrhea based on the data of Semarang City Health Office in 2012 to April 2013 there were 198 cases of diarrhea. This study aims to identify the application of integrated waste management in Sub Tembalang This study is a descriptive study using a qualitative approach to the collection of data through observation depth interview. Subjects taken by purposive sampling, a total of 8 people each RW is in the Village Tembalang, 2 officers garbage collector and three informants triangulation. Analysis of the data using interactive model analysis technique used is content analysis. These results are the source of waste generation from the activities of the household population and non- domestic activities. Operating technic is by shelter, the collection, and transportation. Organic waste processing activities carried residents from 8 RW 2 RW available (25%) and inorganic waste processing done PKK. Community participation in the form of retribution for the collection, sorting garbage, sewage treatment, and the provision of bins. The integration of waste management is a form of guidance, cooperation and partnership in supply/procurement of waste management facilities